(untitled) ("Journal "U". Economy. Management. Finance.", 2017)
The article provides answers to topical issues in the field of marketing. The view of development of the Modern Marketing is proposed in the paper. Topical issue of training of marketing professionals is considered and connected with the existing need in the market for highly qualified personnel. The author gives the forecast of development of marketing.